Relationship between smoking, excessive androgen and negative emotions in women with polycystic ovary syndrome (PCOS) - Yang Yang; Hua Zhang; Bo-Yun Huang; Yong-Hao Lu; Ii Fukuzawa; Shuhan Yang; Lifei Zhou; Liyan Luo; Chunyong Wang; Ning Ding; Sai Li; Li Shi; et al. (BMC, 2024)
Abstract Background Lifestyle intervention is the first-line treatment for PCOS. Numerous studies have investigated the effect of various lifestyle factors, including dietary habit, smoking, and alcohol consumption on PCOS women. These studies have found that such factors may be associated with physiological parameters such as androgen, and emotional states like anxiety or depression. Smoking, a harmful lifestyle habit widely recognized to contribute to various diseases, has also been found to be related to PCOS. Current research has not adequately compared the effects of smoking with other lifestyle habits on PCOS, and there is little mention of its relationship with the emotional states of patients with PCOS. To further elucidate the association between smoking and other lifestyle factors with clinical symptoms in patients with PCOS, we conducted a cross-sectional evaluation using data from Peking University Third Hospital, with a special focus on analyzing smoking habits and comparing it with a variety of lifestyle factors. Methods This cross-sectional study included 601 PCOS women and 184 healthy controls who underwent physical examinations, hormone profiles and psychological measures. We assessed the association between smoking and the clinical symptoms in PCOS women. Results We found a significant correlation between smoking and the degree of depression in PCOS women among the three emotional states: anxiety, depression, and stress. Smoking was also significantly associated with testosterone level in PCOS participants, suggesting that PCOS women who smoke exhibited more severe depressive symptoms and higher testosterone level. In addition, compared to the control group, PCOS women had notably higher testosterone (T) and luteinizing hormone (LH) levels. Smoke and alcohol were statistically significantly more common in women with PCOS than the Control. Conclusion Women with PCOS who smoke were found to have elevated testosterone levels and more severe depression. These findings suggest that clinicians should monitor smoking women with PCOS for symptoms of depression and assess their hyperandrogenic status.